Evaluating the wage differential between the formal and informal economy: a gender perspective. Issue 4 (25th May 2021) - Williams, Colin; Gashi, Ardiana
Abstract : Purpose: Despite a widespread assertion that wages are lower in the informal than formal economy, there have been few empirical evaluations of whether this is the case and even fewer studies of the gender variations in wage rates in the formal and informal economies. Consequently, whether there are wage benefits to formal employment for men and women is unknown. The aim of this paper is to evaluate the wage differential between formal and informal employment for men and women. Design/methodology/approach: To evaluate the wage differential between the formal and informal economy for men and women, data are reported from a 2017 survey involving 8, 533 household interviews conducted in Kosovo. Findings: Using decomposition analysis and after controlling for other determinants of wage differentials, the finding is that the net hourly earnings of men in formal employment are 26% higher than men in informal employment and 14% higher for women in formal employment compared with women in informal employment. Practical implications: Given the size of the wage differential, the costs for employers will need to significantly increase in terms of the penalties and risks of detection if informal employment is to be prevented, along with more formal employment opportunities using active labour market policies for vulnerable groups, perhaps targeted at men (who constitute 82.8% of those in informal employment). Originality/value: This is one of the first studies to evaluate the differentials in wage rates in the formal and economy from a gender perspective.